The effects of polyester microfibres on the development and seed yield of white mustard (Sinapis alba L.) - Harrison, Eleanor Grace; Reiling, Kevin; Halfpenny, Richard Kenneth; Gwinnett, Claire (Frontiers in Environmental Science, 2024)
Microplastics are found in agricultural soils worldwide; however, little is known about the impacts of this ubiquitous pollutant on the growth and development of crops. Microfibres are one of the dominant microplastic types found in agricultural soils. Sources of microfibres in the agricultural environment are multiple, including soil amendment applications, wastewater irrigation and atmospheric deposition, with agricultural soils subsequently acting as an accumulating sink for plastics. A key consideration in an agricultural setting is yield; the seed yield is critical, as this is the part with economic value. This study investigates the influence of polyester microfibres, a prevalent type of microplastic in agricultural soils, on the growth and seed yield of Sinapis alba (white mustard). Polyester microfibres were added to soil samples at concentrations of 0.1% and 1% w/w, simulating environmental exposure levels. The study evaluated flower production, seed yield, pod-to-seed ratio, and chlorophyll fluorescence as indicators of plant health and reproductive success. Results revealed significant changes in chlorophyll fluorescence values (Fv/Fm), reduced flower production control (74 ± 37 flowers in the control, 31 ± 27 in the 0.1 treatment and 44 ± 31 in the 1 % treatment), and changes in pod-to-seed ratio (3.5 ± 0.65 seeds per pod in the control, 2.76 ± 0.5 seeds per pod in the 0.1% treatment and 2.83 ± 0.81 seeds per pod in the 1% treatment) in response to polyester microfibre exposure. Polyester microfibres were demonstrated to act as a stressor to S. alba, changing the chlorophyll fluorescence values, reducing the flower number, and in turn, reducing the pod-to-seed ratio. This study provides evidence that microfibres could reduce seed yield but that further research is required to elucidate the mechanisms by which these changes are occurring.